2012
DOI: 10.1177/1087054711435362
|View full text |Cite
|
Sign up to set email alerts
|

Is ADHD a Risk Factor Independent of Conduct Disorder for Illicit Substance Use? A Meta-Analysis and Metaregression Investigation

Abstract: The existing data do not indicate that ADHD increases the risk of ISU beyond the effects of CD/ODD. However, the combination of all existing data is limited in power to detect a small increase in chance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 60 publications
3
29
0
4
Order By: Relevance
“…Merikangas et al 1998). Attention deficit / hyperactivity disorder (ADHD) is also commonly reported by individuals with SUD (Szobot et al 2007), and some studies have indicated that the link between SUDs and ADHD is usually through conduct disorder or antisocial personality disorder (Disney et al 1999;Elkins et al 2007;Serra-Pinheiro et al 2013).…”
Section: Comorbiditymentioning
confidence: 99%
“…Merikangas et al 1998). Attention deficit / hyperactivity disorder (ADHD) is also commonly reported by individuals with SUD (Szobot et al 2007), and some studies have indicated that the link between SUDs and ADHD is usually through conduct disorder or antisocial personality disorder (Disney et al 1999;Elkins et al 2007;Serra-Pinheiro et al 2013).…”
Section: Comorbiditymentioning
confidence: 99%
“…81 However, a meta-analysis of 1,000 individuals found that ADHD alone might not be an independent risk factor for substance use (RR = 1.35 [0.90-2.03]) when CD and ODD are excluded. 82 Panic disorder predicts alcohol use in adolescence and adulthood, while social phobia is associated with alcohol and cannabis. 83,84 Bipolar disorder and depression are important risk factors, and they often precede substance use in childhood and adolescence.…”
Section: Psychiatric Comorbiditiesmentioning
confidence: 99%
“…In this context, there is still no consensus on the question whether the ADHD inattention symptoms or the ADHD hyperactivity/impulsivity symptoms are more predictive of substance problems [7][8][9]. In addition, some studies found a direct association between ADHD and substance abuse [10], while others demonstrated that this relationship disappears when cooccurring conduct disorder (CD) is taken into account [8,11,12]. Flory et al [3] noted that any observed association between ADHD and substance abuse not considering the overlap of ADHD with CD may be spurious.…”
Section: Introductionmentioning
confidence: 99%
“…Yet because the sample consisted of mainly marijuana or marijuana plus cocaine users, the results might not apply to subjects with a different profile of substance abuse or disorders. Furthermore, a meta-analysis and meta-regression investigation concluded that ADHD did not increase the risk of illicit substance use beyond the effects of CD/ODD [11].ADHD can be defined as extreme values along quantitative dimensions of inattention and hyperactivity/impulsivity [8]. Some studies showed that mainly the inattention symptoms are predictive of substance problems [43,9], while other studies demonstrated that the hyperactivity/impulsivity symptoms are most predictive [44,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation